2012
DOI: 10.1159/000336797
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Acne versus Mosaic Conditions with Acne Lesions

Abstract: Acne rarely presents in segmental patterns, which are encountered only in cutaneous mosaicism. We report herein two cases of segmentally arranged acne and systematically review the literature on the topic. Beside already known mosaic conditions which may show primary lesions typical of acne, i.e. nevus comedonicus, Happle-Tinschert syndrome, acne superimposed on epidermal nevi and mosaic Apert syndrome, we introduce the possibility that acne itself may present in a mosaic form. As from the extremely small casu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Acne is also a feature of several genetic conditions, including monogenic disorders such as autoinflammatory syndromes or Apert syndrome. Several mosaic forms of acne have been described clinically . The underlying molecular mechanisms remain mostly hypothetical and have only been explored in a few cases of mosaic manifestation of Apert syndrome .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acne is also a feature of several genetic conditions, including monogenic disorders such as autoinflammatory syndromes or Apert syndrome. Several mosaic forms of acne have been described clinically . The underlying molecular mechanisms remain mostly hypothetical and have only been explored in a few cases of mosaic manifestation of Apert syndrome .…”
mentioning
confidence: 99%
“…Several mosaic forms of acne have been described clinically. 2,3 The underlying molecular mechanisms remain mostly hypothetical and have only been explored in a few cases of mosaic manifestation of Apert syndrome. 4,5 Here we report a 12year-old boy who developed early, severe acne on pre-existent hypopigmentations distributed along Blaschko lines on the trunk, arms and face.…”
mentioning
confidence: 99%
“…In view of the palmar involvement, we considered other rare conditions with similar morphology, such nevus trichilemmocysticus, Happle Tinschert syndrome (basaloid follicular hamartomas with comedo‐like plugs), segmental acne, and mosaic Apert's syndrome, as possible differential diagnoses . Characteristic histopathology discounted the first two possibilities in our patient and onset at birth ruled out the third.…”
Section: Discussionmentioning
confidence: 72%
“…Men and women are equally affected . A recent review discussed a few rare conditions with mosaic acneiform lesions, some of which may be related pathogenetically to tyrosine kinase receptor signalling pathways . We report a case of nevus comedonicus distributed over the left half of the body, including the palm, without any associated systemic abnormalities and briefly review the recent literature on mosaic conditions with acneiform lesions and their pathogenesis.…”
mentioning
confidence: 95%
“…A review of 375 cases demonstrated that most patients (n = 349) were affected by nevus comedonicus, all following the lines of Blaschko. 2 In relation to the association with BN, only 10 cases were described, all in the thoracic region with a block-like configuration, none of them following the lines of Blaschko. 2 …”
mentioning
confidence: 99%